Marketing Strategy for Hajj Bailout Fund Products at PT. BPRS Aman Syariah - Imas Nur Kholifa; Eki Tiyas Nurulia; Norikha Pandayahesti Saputeri (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2024)
The increasing growth and development of sharia banking in Indonesia will encourage banks to always optimize their marketing activities. The business carried out by Bank PT. BPRS Aman Syariah in facing competition is by providing products and services that can meet the needs of the community, one of which is by providing Hajj bailout financing products. The formulation of the problem in this research is How does PT. BPRS Aman Syariah formulates its marketing strategy for Hajj bailout fund products? The method adopted is qualitative research, aimed at understanding phenomena related to the experience studied, through analysis and description of the marketing strategy for PT's Hajj bailout funds. BPRS Aman Syariah, draws comprehensive insights from analyzed and interpreted data to find product marketing strategies. The results of this research indicate that the implementation of the marketing strategy for Hajj bailout products from aspectsWith relatively satisfactory service differentiation, Bank Aman Syariah also has a good image in the minds of consumers.Marketing mix aspect, PT. BPRS Aman Syariah applies each marketing mix concept, namely: product, price, location or place, promotion, obstacles faced by Bank PT. BPRS Aman Syariah in marketing Hajj bailout products means that the public does not yet know how the operational system is for financing Hajj bailouts and the public does not yet know what benefits they can get from financing Hajj bailouts. The location between one sub-district and another is very wide; The high Ujroh from the first, second and third years becomes an obstacle in marketing Hajj bailout products. Very long queue from the Ministry of Religion to perform the Hajj